Three fatalities associated with the synthetic cannabinoids 5F-ADB, 5F-PB-22, and AB-CHMINACA. (December 2017) - Angerer, V.; Jacobi, S.; Franz, F.; Auwärter, V.; Pietsch, J.
Graphical abstract: Highlights: Three case reports in the context of synthetic cannabinoids are presented. Post mortem femoral blood concentrations are reported. Femoral blood concentrations cannot be correlated directly with the cause of death. Every fatality involving synthetic cannabinoids should be assessed on a case by case basis. Abstract: The use of synthetic cannabinoids (SC) has been widespread in certain groups of drug users for many years. In the scientific literature many intoxication cases and a number of fatalities after the use of synthetic cannabinoids were reported. In this paper three death cases are described with involvement of the synthetic cannabinoids 5F-PB-22, AB-CHMINACA, and 5F-ADB. The three cases occurred in the eastern region of Germany, which is known as a region of high methamphetamine abuse. All decedents were male, between 25 and 41 years old, and had a known history of drug use. Femoral blood concentrations of the synthetic cannabinoids were measured using a validated LC–MS/MS method. The concentration of 5F-PB-22 in the first case was 0.37 ng/mL, the concentration of AB-CHMINACA in the second case was approximately 4.1 ng/mL (extrapolated) and the 5F-ADB concentration in the third case was 0.38 ng/mL. Compared to other published cases the concentrations in the here presented cases seem to be in the lower range. However, taking into account the scene of death, the results of the forensic autopsy and the full toxicological analysis, the deaths can be explained as a direct consequence of consumption of synthetic cannabinoids, although in case one and two relevant amounts of ethanol were found, and in case three trimipramine and olanzapine were present in non-toxic concentrations. It has to be noted that concentrations of synthetic cannabinoids in femoral blood cannot directly be judged as toxic or lethal due to the possibility of postmortem redistribution and the development of tolerance after frequent use. Therefore, all available information has to be considered carefully before stating SC use as the cause of death.